الجانب الإلهي عند سعديا الفيومي من خلال كتابه"الامانات والاعتقادات"-دراسة وصفية مقارنة - نصيره عماره (University of Eloued جامعة الوادي, 2023)
إن العلوم والمعارف والآداب والفنون والعمران في كل دورة حضارية لا تُنتج ابتداء في الغالب، بل هي استمرار لما أنجزه الإنسان المعرفي والعلمي والعملي سابقاً، ودليل ذلك الحضارة الإسلامية، حيث ظهر فيها من بين تلك المجموعات العرقية والعقدية من استنار بعلومها، كاليهود مثلاً، فظهر بينهم علماء في شتى المعارف، من ذلك سعديا الفيومي وغيره، في استعمال طرق ومناهج العلوم الدينية أو النصوص الدينية وما تحمله من عقائد وتشريعات وأخلاق عند علماء المسلمين، حيث أسقطوها على نصوصهم الدينية وعقائدهم وطقوسهم وتشريعاتهم. وكانت هذه الدراسة لبيان الأثر العلمي والمنهجي الذي تركته البيئة الإسلامية على تفكير سعديا الفيومي، في إثبات والاستدلال على أصول عقيدته الدينية من هجمات خصومها من داخل وخارج الملّة اليهودية من خلال مؤلّفه "الامانات والاعتقدات" . The knowledge, literature, arts and architecture in every session civilized, often not initially produced, it is a continuation of what the knowledgeable, scientific and practical person has previously accomplished, The evidence for that is the Islamic civilization. Where scholars appeared among them in various fields of knowledge. As it appeared among those ethnic and ideological groups who were enlightened by their sciences, like jews, for example, Scholars of all kinds appeared among them. From that Saadia Al-Fayoumi and others, In using the methods and curricula of religious sciences, Or religious texts and their doctrines and legislation morals of Muslim scholars, They dropped it on their religious texts, beliefs, rituals and legislation. This study was to demonstrate the scientific and methodological impact, which the Islamic environment left on the thinking of Saadia al-Fayoumi, In proving and inferring the origins of his religious belief from the attacks of its opponents Inside and outside the Jewish community. Through his authorship of "Opinions and beliefs
The Divine Side Of Saadia Fayoumi Hrough His Book " Beliefs And " Opinions" A Descriptive Comparative Study
Keywords: الحضارة الإسلامية؛ اليهود؛ سعديا؛ مناهج; Methods; Islamic civilization; Jews; Saadia